Enforcement Law Enforcement of Thrifting Practices in Purwokerto - Eka Putri, Nur Aziah; Wati, Ratna Kartika (Universitas Muhammadiyah Gresik, 2024)
This research aims to discuss the mechanism of thrifting in Purwokerto area, as well as to examine law enforcement against thrifting practices carried out in Purwokerto. The research method used in this research is normative juridical with a statue approach or statutory approach. This research uses data collection methods in the form of literature study and qualitative analysis methods. The results of this study are first, the thrifting mechanism through the Supplier Selection process, Sorting Process, Washing / Cleaning, Affixing Price Tags, Arranging Goods. Second, law enforcement as stipulated in Law Number 7 of 2014 concerning Trade (Trade Law), Regulation of the Minister of Trade Number 40 of 2022 concerning Amendments to Regulation of the Minister of Trade Number 18 of 2021 concerning Goods Prohibited from Export and Goods Prohibited from Import has actually prohibited the trade in second-hand goods. However, the implementation and enforcement of these regulations still face many obstacles, especially in terms of monitoring and supervision of buying and selling activities. More specific and clear regulations on the secondhand clothing trade are needed to address the complexities that exist in the practice of thrifting in Indonesia.